Application of surfactant modified montmorillonite with different conformation for photo-treatment of perfluorooctanoic acid by hydrated electrons. (November 2019) - Chen, Zhanghao; Tian, Haoting; Li, Hui; Li, JianSheng; Hong, Ran; Sheng, Feng; Wang, Chao; Gu, Cheng
Abstract: Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are a class of highly persistent contaminants with high bioaccumulation and toxicity. Our previous studies showed that perfluorooctanoic acid (PFOA) can be completely defluorinated under UV irradiation in organo-montmorillonite/indole acetic acid (IAA) system. However, there is still lack of information for the degradation mechanism and the test for wastewater treatment. Here, we systematically investigated the defluorination reaction in the presence of different organo-montmorillonites and found that the degradation process was apparently controlled by the configuration of surfactants. In hexadecyltrimethyl ammonium (HDTMA)-modified montmorillonite, HDTMA exists as a tilt conformation and isolated clay interlayer from the aqueous solution, protecting hydrated electrons generated by photo-irradiation of IAA from quenching by oxygen. Defluorination hydrogenation process was the dominant degradation pathway. While in poly-4-vinylpyridine-co-styrene (PVPcoS)-modified montmorillonite, due to the multiple charges of PVPcoS, a flat conformation parallel to clay surface was expected. Hydroxyl radicals, which were generated by the reaction of hydrated electrons with oxygen molecules diffused into clay interlayer, are also involved in the degradation process. Our results further demonstrate that mixture modified montmorillonite could combine the advantages of both modifications, thus showing superior reactivity even for actual industrial wastewater without any pretreatment. This technique would have great potential for treatment of actual wastewater. Graphical abstract: Image 1 Highlights: HDTMA and PVPcoS modified montmorillonites were studied for treating PFOA wastewater. The PFOA degradation process was apparently controlled by the configuration of surfactants. A mixture modified montmorillonite combining the advantages of both modifications showed superior reactivity. The mixed modified montmorillonite system showed superior reactivity even for actual industrial wastewater.